2013
DOI: 10.1002/jgra.50151
|View full text |Cite
|
Sign up to set email alerts
|

On the storm‐time evolution of relativistic electron phase space density in Earth's outer radiation belt

Abstract: [1] We report on internal, magnetospheric processes related to markedly different storm-time responses of phase space density (PSD) in invariant coordinates corresponding to equatorially mirroring, relativistic electrons in Earth's outer radiation belt. Two storms are studied in detail, selected from a database of 53 events (Dst min < À40 nT) during the THEMIS era thus far (December 2007-August 2012. These storms are well covered by a number of in situ THEMIS spacecraft and complemented by additional ground-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
168
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 135 publications
(190 citation statements)
references
References 98 publications
16
168
2
Order By: Relevance
“…Neglecting mixed diffusion (which can be important too) [see Albert , ] and assuming an initially cold distribution without high‐energy electrons (for instance, just after dropouts) [e.g., see Turner et al , , and references therein], the energy broadening of the electron distribution F ( E , t ) in the presence of quasi‐linear energy diffusion by quasi‐parallel whistler mode waves is given approximately by [ Horne et al , ; Balikhin et al , ] ∂F∂t=∂E(A(E)DEE(F/A(E))∂E)FτLwhere A(E)(E+0.511)E(E+1) with E in MeV.…”
Section: Analytical Expressions Of the Trapped Electron Distributionmentioning
confidence: 99%
“…Neglecting mixed diffusion (which can be important too) [see Albert , ] and assuming an initially cold distribution without high‐energy electrons (for instance, just after dropouts) [e.g., see Turner et al , , and references therein], the energy broadening of the electron distribution F ( E , t ) in the presence of quasi‐linear energy diffusion by quasi‐parallel whistler mode waves is given approximately by [ Horne et al , ; Balikhin et al , ] ∂F∂t=∂E(A(E)DEE(F/A(E))∂E)FτLwhere A(E)(E+0.511)E(E+1) with E in MeV.…”
Section: Analytical Expressions Of the Trapped Electron Distributionmentioning
confidence: 99%
“…Recently, the paradigm for explaining the enhancement of the electron radiation belt has shifted from the almost exclusive use of the theory of radial diffusion to a greater emphasis on the role of waves in the in situ heating of radiation belt electrons. The waves are produced by the injection of plasma‐sheet electrons into the inner magnetosphere [ Horne and Thorne , ; Shprits et al ., ; Chen et al ., ; Kasahara et al ., ; Bortnik and Thorne , ; Yoon , ; Turner et al ., ; Reeves et al ., ]. Though it has become generally accepted that both mechanisms can energize radiation belt electrons, their relative contributions remain uncertain.…”
Section: Introductionmentioning
confidence: 98%
“…However, it has now been shown that dropouts can also occur independent of geomagnetic storms [e.g., Morley et al, 2010] and that the adiabatic effects alone cannot explain the magnitude of loss observed during dropouts [e.g., Kim and Chan, 1997;Li et al, 1997]. The clearest evidence that outer belt dropouts are driven by true losses from the system (i.e., not just adiabatic effects) have resulted from studies of events, revealing that distributions of electron phase space density (PSD) in adiabatic invariant coordinates, which remove most of the ambiguity due to purely adiabatic effects, also undergo outer belt dropouts [e.g., Turner et al, 2013]. Here we use the definition of dropouts described in Turner et al [2012b], which includes both adiabatic effects and nonadiabatic losses.…”
Section: Introductionmentioning
confidence: 99%